The Effect of Foaming Agent and Whipping Time on Albedo Characteristics of Watermelon Flour - Setiyoko, Agus; Putri, Soraya Kusuma (Journal of Agri-Food Science and Technology, 2023)
The fruit's rind is one of the natural waste products that can support nutrients like carbohydrates, proteins, and lipids. Reused rind contributes significantly to the effective handling of this fruit's byproduct. Processing watermelon rind into powder by lowering water content and activity is an alternative to extending its shelf life. The flour form is easier and more suitable for application in multiple processing food products such as snacks, beverages, bread, and pasta. The focus of this study was to verify the optimal state for foam mat drying using concentrations of foaming agent in the form of egg albumin (10, 15, 20), foam stabilizer in the form of CMC with concentrations of 1 %, and whipping time (5, 7, and 9 minutes) on for bulk density, WSI, hygroscopicity, L* value, a* value, b* value of total phenol and antioxidants activity, and the maximum antioxidant content of watermelon albedo flour using Completely Randomized design with 2 factorial resulting in nine treatments with three replications. Based on the outcome, the bulk density of the resulting watermelon albedo flour ranges from 0.25-0.50 gr/cm-3 and 0.11-0.26%. of WSI; 22.63-28.18g/100g-1 of hygroscopicity; 1.92-4.67% of total phenol; 47.48-66.59% of L*value; 3.74-6.11% of a*value; 5.47-16.08% of b*values and 6.80- 25.26% RSa of antioxidants activity. The best treatment for antioxidant activity was 25.26% RSA using 10% of the foaming agent and whipping time in 9 minutes. These findings have implications for the food industry because they suggest that treatments can influence the properties of watermelon albedo flour.